2020
DOI: 10.1111/1346-8138.15550
|View full text |Cite
|
Sign up to set email alerts
|

Case of autosomal recessive woolly hair/hypotrichosis with a homozygous c.736T>A mutation of LIPH caused by maternal uniparental disomy of chromosome 3

Abstract: we speculate that expression of MREG suppresses melanogenesis more in the RPE than in other parts of melanocytes of patients with impaired BLOC-2. When this paper was being reviewed, Pennamen et al. 1 reported a new type of HPS, HPS11, caused by distinct homozygous variants of the BLOC1S5 gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In recent years, studies related to LIPH have mostly focused on the mutations in the LIPH gene, which can cause a rare form of congenital hair loss called autosomal recessive woolly hair/hypotrichosis (ARWH/H). 10 , 24 , 25 However, the role of the novel cancer-related gene LIPH in several carcinomas has been reported in some studies. The expression of LIPH was correlated with the amount of esophageal tumors, but not with the metastasis, and Ishimine et al 14 further confirmed these characteristics using three independent esophageal adenocarcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, studies related to LIPH have mostly focused on the mutations in the LIPH gene, which can cause a rare form of congenital hair loss called autosomal recessive woolly hair/hypotrichosis (ARWH/H). 10 , 24 , 25 However, the role of the novel cancer-related gene LIPH in several carcinomas has been reported in some studies. The expression of LIPH was correlated with the amount of esophageal tumors, but not with the metastasis, and Ishimine et al 14 further confirmed these characteristics using three independent esophageal adenocarcinoma cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…8 Previous studies mostly focused on the mutation and correlation of LIPH, which is the main reason for autosomal recessive woolly hair/hypotrichosis. [9][10][11] Recent years, studies of LIPH on cancers have been increasingly investigated. Orozco-terWengel et al 12 showed that the expression of LIPH was related to immunity in cattle.…”
Section: Introductionmentioning
confidence: 99%
“…Among the 10 cases of maternal UPD(3) with an abnormal phenotype, 6 had clear clinical phenotypes associated with chromosomal recessive disorders, 2 had abnormal chromosome karyotype, 1 had mosaic UPD, and detailed information was not available for 1 case. Among these six cases, the phenotypes included epidermolysis bullosa ( COL7A1 ) [ 9 , 10 ], Fanconi Bickel syndrome ( GLUT2 ) [ 11 ], a congenital disorder of glycosylation type Id ( ALG3 ) [ 12 ], GM1 gangliosidosis ( GLB1 ) [ 13 ], and woolly hair/hypotrichosis ( LIPH ) [ 14 ]. Among the five reported cases of paternal UPD(3), three had a definite phenotype caused by single-gene disorders, one had no apparent disease phenotype, and one presented an abnormal karyotype.…”
Section: Discussionmentioning
confidence: 99%